Somatotype and anthropometry in brazilian national volleyball teams - Breno Guilherme de Araújo Tinoco Cabral; Suzet de Araújo Tinoco Cabral; Gilmario Ricarte Batista; Jose Fernandes Filho; Maria Irany knackfuss (Desafio Singular, 2008)
The elaboration of profile characteristics that can serve as parameters in the different categories and investment in scientific studies of Brazilian volleyball have shown their importance in developing new athletes. In this sense, the objective of the descriptive study in question was to analyze important characteristics such as somatotype and anthropometry in the Brazilian under-17 and under-18 national teams, respectively. The population was composed of 33 (14 females and 19 males) athletes from the aforementioned teams. We used a high-precision scale and stadiometer to verify anthropometric characteristics and Heath & Carter's method to evaluate somatotype. The men's team obtained the following mean results: Age=16.71; height=195.9cm; body weight=87.7kg; endomorphy=1.26; mesomorphy=3.18 and ectomorphy=3.8; while the women's results were: Age=15.9; height=181.6cm; body weight=67.4kg; endomorphy=3.09; mesomorphy=2.21 and ectomorphy=3.88. We can conclude from the results that the teams in question have similar characteristics to those of the high-performance adult teams, and exhibit a predominance of the ectomorphic component of the somatotype. This finding is of great importance, given the current demands of high-performance volleyball, and shows us the high level of the group studied.